Apparent digestibility coefficients of selected protein feed ingredients for loach Misgurnus anguillicaudatus. (16th October 2014) - Chu, Z.J.; Yu, D.H.; Yuan, Y.C.; Qiao, Y.; Cai, W.J.; Shu, H.; Lin, Y.C.
Abstract Apparent digestibility coefficients of dry matter, crude protein, lipid and energy, and amino acids availability in white fish meal, brown fish meal, meat meal, fermented soybean meal, soybean meal and rapeseed meal were determined for loach (Misgurnus anguillicaudatus) (12.05 ± 0.21 g), using a reference diet with 5 g kg−1 chromic oxide and test diets that contained 700 g kg−1 reference diet, by weight, and 300 g kg−1 of the test feed ingredients. The juvenile loach was held in 300‐l tanks at a density of 30 fish per tank. White fish meal, brown fish meal, meat meal and fermented soybean meal had highest apparent digestibility coefficients (ADCs) of dry matter, crude protein and gross energy among ingredients tested, ranged from 50.4% to 60.9% for dry matter, from 64.6% to 88.4% for crude protein and from 57.9% to 79.0% for gross energy. The apparent digestibility coefficients of dry matter ranged from 61.0% to 66.9% for animal products and 50.4% to 60.7% for plant products. For crude protein, apparent digestibility coefficients of protein exceeding 80% were observed for white fish meal, brown fish meal, meat meal and fermented soybean meal, and the apparent digestibility coefficients of protein in rapeseed meal were the lowest among all the treatments. Lipids from both animal and plant feedstuffs were poorly digested by loach, ranging from 64.0% to 77.6%. The apparent digestibility coefficients of energy were similar to those of dry matter and protein, and the highest and lowest ADCs of energy were found in WFM and RM, respectively. The loach used dietary phosphorus from the animal feedstuffs more efficiently than from plant feedstuffs (soybean meal and rapeseed meal), with ADC‐values ranging from 42.3% to 53.1% and from 25.1% to 32.7%, respectively. For the animal products, the availabilities of amino acids in white fish meal and brown fish meal were higher than that in meat meal, expect for Met, Asp, Pro, Gly, and Cys. Among all the plant products, the availabilities of amino acids in fermented soybean meal were higher than in soybean meal and rapeseed meal, and thus had a greater potential to be used as a dietary replacement of fish meal in loach diets.